European private equity funds: A cash flow based performance analysis - Christian Diller; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2004)
This paper presents a cash flow based analysis of the return and risk characteristics of European Private Equity Funds. For that purpose a comprehensive data set has been provided by Thomson Venture Economics. We document the typical time pattern of cash flows for European private equity funds. Specifically, it is recorded that the average European private equity fund draws down 23% of total committed capital on the vintage date; within the first three years 60% of the total commitment is draw down. It turned out that limited partners on average get back the money invested slightly after 7 years. Over the time period from 1980 to June 2003, we calculate various performance measures. For that purpose we use only liquidated funds or funds with a small residual net asset value. Under this restriction one specific data set consists of 200 funds. We document a cash flow based IRR of 12.7% and an average excess-IRR of 4.5% relative to the MSCI Europe equity index. In order to circumvent the problems associated with the IRR-approach we focus on the alternative public market equivalent approach. There it is assumed that cash flows generated by a private equity fund are reinvested in a public market benchmark index. We record an average PME of 0.96 and a value-weighted average PME of 1.04. Based on the PME-approach we develop a viable methodology to estimate the return and risk characteristics of European private equity funds and the correlation structure to public markets. As a benchmark index we used the MSCI Europe Equity Index as well as the J.P.Morgan Government Bond Index. Over the period 1980-2003 private equity funds generated an overperformance with respect to the bond index and two of our three samples an underperformance with respect to the equity index. Over the period 1989-2003 private equity funds generated an overperformance with respect to both indexes. Finally, we analyze to what extent performance measures are associated with specific funds characteristics, like size, payback period and vintage year, respectively. While the payback period and the vintage year seem to have a statistically significant influence on a fund's performance, the results with respect to size are inconclusive.
Keywords: G24; 330; private equity; venture capital; cash flow analysis; public market equivalent; internal rate of return